Diabetes treatment patterns and goal achievement in primary diabetes care (DiaRegis): study protocol and patient characteristics at baseline - Bramlage, Peter; Binz, Christiane; Gitt, Anselm Kai; Krekler, Michael; Plate, Tanja; Deeg, Evelin; Tschöpe, Diethelm (Cardiovascular diabetology, 2010)
Patients with type 2 diabetes are at an increased risk for disease and treatment related complications after the initial approach of oral mono/dual antidiabetic therapy has failed. Data from clinical practice with respect to this patient group are however scarce. Therefore we set up a registry in primary care documenting the course and outcomes of this patient group.
Gesehen am 15.02.2023